RELEVANSI NILAI INFORMASI AKUNTANSI: SUATU KAJIAN TEORITIS - Naimah, Zahroh (Buletin Studi Ekonomi; VOL.19.NO.1.FEBRUARI 2014.(PP 1-117), 2016)
The value relevance of Accounting Information (Theoritical Reviews). This paper theoritically reviews the value relevance of accounting information and the research development of the value relevance of accounting information. The value relevansi accounting information comprises of the the value relevance of accounting earnings, the value relevance of asset and liabilities, the value relevance of accounting earnings and book value of equity. This paper also theoritically reciews the factors that influence the value relevance of accounting information. The value relevance of accounting earnings is influenced by earnings quality, capital structure, auditor quality, company’s risk, firm’s size, growth opportunuty, and earnings persistence. The value relevance of accounting earnings and book value of equity is influenced by negative earnings, earnings persistence, financial health, profitability and growth opportunity, accounting conservatism, and investment in intangible assets.   Keywords: value relevance, accounting earnings, book value of equity, earnings response coefficient.
Keywords: value relevance, accounting earnings, book value of equity, earnings response coefficient.